Epstein-Barr Virus–associated Mucocutaneous Ulcer in a Patient With T-Cell Acute Lymphoblastic Leukemia: Importance of Accurate Diagnosis and Conservative Management. Issue 6 (August 2017) - Vatsayan, Anant; Gupta, Ashish; Ahuja, Sanjay; Egler, Rachel; Beck, Rose C.; Matloub, Yousif
Abstract : Epstein-Barr virus–associated mucocutaneous ulcer (EBV-MCU) is a recently characterized entity that falls under the spectrum of EBV-lymphoproliferative disorders. First described in 2010 by Dojcinov et al, it is an EBV-driven localized proliferation of B cells, occurring in mucocutaneous tissues including the skin, the oropharynx, and the gastrointestinal tract of immunosuppressed patients in the absence of an intact T-cell repertoire. Typically, it has been described in elderly patients with age-related immunosenescence and patients who are on immunosuppressive therapy. However, only 2 cases have been reported in pediatric, adolescent, and young adult age groups, with all these patients manifesting after solid organ transplant. To the best of our knowledge there are no case reports of EBV-MCU occurring in association with hematologic malignancy. Here, we present a case of EBV-MCU in a young adult patient with T-cell acute lymphoblastic leukemia. Our report serves to promote awareness among clinicians regarding this newly described and extremely rare clinical entity in young immunosuppressed patients. In addition, we highlight the importance of accurate diagnosis to prevent overtreatment of this indolent, often self-resolving disease that has a significant clinicopathologic overlap with other aggressive forms of EBV-lymphoproliferative disorders that require more intensive therapy.